Effect of Local Anesthetic Injections on Subjective Pain Scales in Pediatric Tonsillectomies: A Meta‐analysis. (5th February 2023) - Stramiello, Joshua A.; Ortega, Briana; Brigger, Matthew; Nation, Javan Jonathon
Abstract: Objective: To assess the effect of local anesthetic injection on subjective pain scores for pediatric tonsillectomies on postoperative days (PODs) 0 and 1. Data Sources: A comprehensive literature search was conducted with the PubMed, Embase, Web of Science, and Scopus databases. Review Methods: A 2‐researcher team following the PRISMA guidelines performed a systematic review and meta‐analysis. Studies with original data and a saline injection control arm were selected. Corresponding authors were contacted for missing data. The collated data were analyzed with RevMan version 5.4 (Review Manager; Cochrane Collaboration). Random effects modeling and standard mean difference were utilized to control for heterogeneity. Surgical technique subgroup analysis was performed. Results: A total of 319 publications were identified, and 8 articles with 13 experimental arms (627 participants) were selected for meta‐analysis. Local anesthetic injection was compared with placebo with saline injection. The standard mean difference for POD 0 pain was −0.81 (95% CI, −1.16 to −0.46; P < .00001) in favor of local anesthetic. The standard mean difference for POD 1 was −1.13 (95% CI, −1.48 to −0.78; P < .00001) in favor of local anesthetic. Subgroup analysis by surgical technique showed a less robust effect for cautery excision (−1.01 [95% CI, −1.37 to −0.66]) vs cold excisional technique (−1.19 [95% CI, −1.64 to −0.74]), with or without cautery‐based hemostasis. Conclusions: A local anesthetic injection during a pediatric tonsillectomy reduces postoperative pain on POD 0 and 1. Further analysis on total narcotic use and postoperative complications would benefit surgeon decision making.